Synthesis and structure activity relationships of a series of 4-amino-1H-pyrazoles as covalent inhibitors of CDK14. Issue 15 (1st August 2019) - Ferguson, Fleur M.; Doctor, Zainab M.; Ficarro, Scott B.; Marto, Jarrod A.; Kim, Nam Doo; Sim, Taebo; Gray, Nathanael S.
Graphical abstract: Abstract: The TAIRE family of kinases are an understudied branch of the CDK kinase family, that have been implicated in a number of cancers. This manuscript describes the design, synthesis and SAR of covalent CDK14 inhibitors, culminating in identification of FMF-04-159-2, a potent, covalent CDK14 inhibitor with a TAIRE kinase biased selectivity profile.